Molecular analysis of BCR-ABL1 fusion transcripts in acute leukemia patients in Southern Odisha, India - Sabat, Sheetal; Naik, Aparupa; Purohit, Prasanta; Bholo, Snehal; Parida, Chinmayee; Patro, Manoj Kumar; Behera, Samira Kumar (Rzeszów University Press, 2026)
Introduction and aim. The occurrence of BCR-ABL1 fusion transcript in acute-leukemia cases are limited and is characterized with various subtypes. This study was based on investigation of the BCR-ABL1 fusion transcript in acute-leukemia cases in a tertiary care hospital. Material and methods. This cross-sectional study was carried out in suspected cases of acute leukemia. Cases were analyzed for complete blood counts, peripheral smear, bone marrow and flow-cytometry for the diagnosis of acute-leukemia. Additionally, diagnosed cases were investigated for BCR-ABL1 fusion transcript by PCR amplification using reverse transcriptase enzyme followed by documentation. Results. Approximately 55 acute leukemia cases included, diagnosed by flow cytometric analysis. Analysis of the BCR-ABL1 fusion-transcript in 55 cases showed its occurrence in only 2 cases, where one case with the B-ALL was characterized with e1a2 subtype and a other case with AML was characterized with the e13a2 subtype. Conclusion. The BCR-ABL1 fusion transcript in acute-leukemia cases was found in 3.64% (2/55) of cases. The diagnosis of BCR-ABL1 fusion transcript in acute-leukemia cases is important for its poor prognosis, as well as calls for the use of ABL tyrosine kinase inhibitors. The diagnosis of BCR-ABL1 fusion-transcript in acute leukemia cases in a tertiary health care facility will be helpful for better treatment of patients in the study area.
This study was approved by the Institutional Ethical Committee (IEC) of M.K.C.G Medical College, Berhampur, Odisha, India. (No. 1381/Chairman-IEC, M.K.C.G. Medical College, Brahmapur-4).
Keywords: acute leukemia; acute lymphoblastic leukemia; acute myeloid leukemia; BCR-ABL1fusion transcript; polymerase chain reaction